Selected Microeconomic Effects of Ict Firms in Context of Level of Sectoral Concentration: Case Study in Selected Regions of the Czech Republic - Turečková, Kamila (Vysoké učení technické v Brně, Fakulta podnikatelská, 2018)
Purpose of the article: It is assumed that a strongly territorially concentrated branch that transformed into the sectoral agglomeration of identical companies in terms of the branches is specific for a range of its network externalities such as positive effects resulting from a qualified workforce, spreading innovation and transferring knowledge, experience and information. In general terms, some microeconomic factors and relevant variables will be perceived differently by ICT firms in the context of the different intensity of the sectoral concentration in the particular territory. Methodology/methods: The contribution is based on the primary research performed among ICT companies in two Czech selected regions expressing their attitudes and opinions in the context of the branch concentration emphasizing the specific localization of these companies within the centres, or on the periphery. The theoretical basis includes in particular „the coreperiphery theory“ and the New Economic Geography extended by the concept of the sectoral agglomerations and also selected theories of the period of post-Fordism. Scientific aim: The presented contribution deals with the specification of the chosen microeconomic effects of the branch con-centration of companies in the ICT sector of the given area, and defines differences in factors of the branch concentration of ICT companies. Findings: Based on the performed research, it was discovered that more than 60 % of the companies perceive branch concentration positively and consider its effect beneficial and desired. From interregional comparisons follows that ICT firms in the Moravian-Silesian Region are more decided towards their employees. South Moravian ICT firms feel less dependent on other ICT firms, but are less aware of their competition. Conclusions: The results of the research reflect the assumptions of the chosen theoretical framework and support the conclusion that it is suitable for ICT companies to do business in a region where the ICT sector is concentrated.
Keywords: Sector Concentration; Effects of Concentration; Information and Communication Technology; Region; Czech Republic